Development of seeder for mixed planting of corn and soybeans - Woo, Seung Min; Uyeh, Daniel Dooyum; Sagong, Moon Sang; Ha, Yu Shin (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Corn and soybeans should be sown between 5 cm and 10 cm apart in mixed cultivation to increase protein content and improve productivity of the forage. However, existing sowers cannot plant at intervals of less than 20 cm. Consequently, mixed cultivation of corn and soybeans is currently performed by first sowing corn seeds with a tractor and then manually planting soybean seeds. This method results in irregular intervals between the seeds, it is laborious and time consuming. This study aimed at developing a seeder that can simultaneously, precisely and efficiently plant corn and soybean. The geometrical and rheological properties of corn and soybeans were initially measured. The seed conveying equipment were designed using the EDEM software. The sowing interval between seeds, depth of soil over planted seed, and sowing performance were analyzed. The EDEM simulation results indicated that a 6-mm-wide and 3-mm-deep grooved seed-delivering roller had the highest particle mobility of the designs considered, with a 2.5% misplanting rate. A performance test showed that no misplanting occurred in the sections sowed with soybean seeds at a seeding interval that averaged 32 mm (321 seeds sown in 10 m) and that misplanting occurred in one section sowed with corn at a seeding interval that averaged 247 mm (40 seeds sown over 10 m). The sowing efficiency for both corn and soybeans was found to be 0.42 h/hm2. The average depth of soil over seed was 32.7 mm for soybean and 39.7 mm for corn. These average depths are within the stipulated range for the depth of soil over seed, which is 5 to 10 times the seed size. This study developed an efficient seeding machine that can simultaneously plant soybean and corn precisely, consequently improving forage yield and saving man-hours. Keywords: corn, geometric characteristics, mixed planting, seeder, soybean DOI: 10.3965/j.ijabe.20171003.2543